Traditional Ulama', Islamic Traditions, and Ngaji Pasanan within the Networked Society - Mohamad Sobirin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
In Ramadan, kiai in various pondok pesantren (Indonesian Islamic Boarding Schools) conduct lecturing activities known as